2014
DOI: 10.1111/1574-6941.12360
|View full text |Cite
|
Sign up to set email alerts
|

Microbial heterotrophic production in an oligotrophic acidic geothermal lake: responses to organic amendments and terrestrial plant litter

Abstract: Boiling Springs Lake (BSL) is an oligotrophic, acidic geothermal feature where even very low levels of microbial heterotrophic production still exceed autotrophy. To test whether allochthonous leaf litter (LL) inputs fuel this excess, we quantified leaf litterfall, leaching and decomposition kinetics, and measured the impact of organic amendments on production, germination and cell growth, using pyrosequencing to track changes in microbial community composition. Coniferous leaves in BSL exhibited high mass los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 94 publications
(158 reference statements)
0
3
0
Order By: Relevance
“…Recently, we also observed that additions of dissolved or particulate organic amendments results in the replacement of chemolithoautotrophs by heterotrophic Firmicutes such as Alicyclobacillus , which likely survive as endospores, or Acetobacteraceae ( Proteobacteria ), which are in part introduced from leaf litter (Wolfe et al. ). These taxa were detected genetically in our protist enrichments (Table ), which were likely fueled by organics leaching from wheat berries.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Recently, we also observed that additions of dissolved or particulate organic amendments results in the replacement of chemolithoautotrophs by heterotrophic Firmicutes such as Alicyclobacillus , which likely survive as endospores, or Acetobacteraceae ( Proteobacteria ), which are in part introduced from leaf litter (Wolfe et al. ). These taxa were detected genetically in our protist enrichments (Table ), which were likely fueled by organics leaching from wheat berries.…”
Section: Discussionmentioning
confidence: 96%
“…A variety of heterotrophs, both prokaryotes and eukaryotes (fungi), feed off allochthonous C inputs from the surrounding montane coniferous forest ecosystem (Wolfe et al. ).…”
mentioning
confidence: 99%
“…The Actinobacteriota phylum, in particular, has the potential to decompose xylogen and cellulose (Eriksson et al ., 1990; Liu et al ., 2020). Additionally, other bacterial families involved in N cycling, such as acetobacteraceae (Proteobacteria phylum) (Qiu et al ., 2021; Wolfe et al ., 2014), are also present in module#15.…”
Section: Discussionmentioning
confidence: 99%